Characterization of Spontaneous Mammary Tumors in Domestic Djungarian Hamsters (Phodopus sungorus). (November 2015) - Yoshimura, H.; Kimura-Tsukada, N.; Ono, Y.; Michishita, M.; Ohkusu-Tsukada, K.; Matsuda, Y.; Ishiwata, T.; Takahashi, K.
Mammary tumors that spontaneously occurred in domestic Djungarian hamsters ( Phodopus sungorus ) were histologically examined. Forty-five mammary tumors included 14 adenomas, 18 adenocarcinomas, 1 lipid-rich carcinoma, 2 adenoacanthomas, 2 malignant adenomyoepitheliomas, 1 benign mixed tumor, and 7 "balloon cell" carcinosarcomas. The latter 4 types were newly recognized neoplasms in Djungarian hamsters. The relatively high incidence of spontaneous mammary carcinosarcomas in domestic Djungarian hamsters is intriguing. Carcinosarcomas exhibited anomalous histological features made up of a mixture of glandular cells, polygonal cells (including "balloon cells"), and sarcomatous spindle cells in varying proportions. Transitional features from glandular cells to polygonal cells and subsequently to sarcomatous spindle cells were observed. Using immunohistochemistry, we observed that glandular cells exhibited an epithelial phenotype (cytokeratin(+)/vimentin(–)), spindle cells exhibited a mesenchymal phenotype (cytokeratin(–)/vimentin(+)), and polygonal cells exhibited an intermediate phenotype (cytokeratin(+)/vimentin(+)). Reduction or loss of β-catenin expression and gain of S100A4 expression were observed in polygonal and spindle cells. The polygonal cell population included a varying number of characteristic cells that were expanded by large intracytoplasmic vacuoles. Electron microscopy revealed that these "balloon cells" had large cytoplasmic lumens lined by microvilli. These observations suggest that epithelial-mesenchymal transition may account for the pathogenesis of mammary carcinosarcomas in Djungarian hamsters.